How young adult consumers evaluate diffusion brands: effects of brand loyalty and status consumption - Phau, Ian; Cheong, Edith (Taylor & Francis Group, 2009)
This paper evaluates how brand loyalty may affect young status consumers' evaluation of diffusion brands for high/low involvement fashion products. In particular, the positioning strategy of the type of diffusion brand names is investigated in this study. Data were gathered through an experimental research design from 739 young status consumers studying in a large university. The findings revealed that sub-brands and nested brands with different country of origins have similar product quality and brand image evaluations compared to the parent brand. This indicates that sub-brands and nested brands may be considered by brand loyal consumers as suitable substitutes for the luxury parent brands. Contrary to literature, there is no difference in findings between high and low involvement fashion products. Implications for marketers are identified.